CUMULATIVE PROPERTIES OF FERRUM(IV) CLATHROCHELATE IN RATS - Dukhnitsky, V. B.; Derkach, I. M.; Derkach, S. S.; Fritsky, I. O.; Plutenko, M. O. (Scientific Progress & Innovations, 2019)
In the system of toxicometric indices it is extremely important to establish the degree of danger of preparations’ chronic effects (cumulative properties) at low intensity of exposure. Such investigations of heavy metal compounds are particularly necessary because, as it is known, they have a pronounced cumulative capacity. The purpose of the research was to study the cumulative properties of high valency ferrum − IV in the form of clathrochelate. Experimental and control groups of white rats were formed for the research, each consisting of 6 animals. Aqueous solution of ferrum (IV) clathrochelate in the amount of 5 ml was administered daily, internally with a metal probe. Animals of the experimental group received the dose starting from 500 mg/kg of body weight, which made 1/10 of the maximum dose. Every four days, the dose of ferrum (IV) clathrochelate was increased by 1.5 times. Animals of the control group were administered isotonic sodium chloride solution in the volume of 5 ml. As a result of the conducted studies, the cumulative index of the investigated complex was determined and it made 6.88 units, which showed its weakly expressed cumulative activity. The control of the body weight change dynamics was made during 24 days of daily administering ferrum (IV) clathrochelate in increasing dosage; at first the body weight increased, and from the 12th day it decreased in comparison with the control group. It was found that the relative coefficient of the heart weight decreased significantly - by 22.7 % (p<0.01), and the relative coefficients of the liver and kidneys weight increased by 22.0 % (p<0.01) and 24 % (p<0.05), correspondingly, as compared with the control. The relative coefficient of the spleen weight decreased by 41% in comparison with the control group, it is probably explained by the development of atrophic processes in this organ. Ferrum (IV) clathrochelate stimulated hemocytopoiesis, which was manifested by increasing the number of erythrocytes, but decreasing hemoglobin levels (p<0.001) and the hematocrit index in animals of the experimental group by 22.7 % and 10 % respectively, as compared with those in the control animal group. In this case, the number of leukocytes decreased by almost 39.0 %, indicating the presence of inflammatory or other pathological processes in the body of rats of the experimental group. The obtained results of blood serum biochemical studies indicated the inhibition of protein synthesizing function in the body of rats, which was confirmed by the indices of alkaline phosphatase activity and the content of total protein and albumins. Glycogenolysis stimulation was established, as glucose index in the blood serum of rats increased by 36.6 % as compared with the control. The increasing of the creatinine content by 8.6 % indicated minor renal dysfunction. Changes in the indices reflecting the functional state of many organs and systems in the body, such as the activity of aspartate and alanine aminotransferases and urea, have not been established. Also, the content of calcium and phosphorus in the blood serum of rats were unchanged. The foregoing information points to material cumulation as its variety, which is typical for heavy metal cumulation.